Pengaruh Asap Rokok Elektronik (E-Cigarettes) Dan Konvensional Terhadap Trakea Dan Jantung Tikus Putih Jantan - andari, desy; Kharimah, Yusrotun; Harianja, Ade Friskilla; Pravitasari, Dwi Nurwulan (E-Jurnal Medika Udayana, 2023)
Electronic cigarettes (e-cigarette) smoker was increasing from 0.3% in 2011 to 2.5% in 2015. E-cigarettes claimed to be safe for smoker, but subsequent research has shown that e-cigarette smoke also contains harmful ingredients beside nicotine, like carbon monoxide (CO). These contents presumed to increase the goblet cells in the trachea and can cause myocardial ischemia in the left ventricle of the heart which leads to necrosis. This study was conducted to determine the effect of e-cigarette and conventional cigarette smoke on tracheal goblet cells and left ventricular necrosis of the heart of male white rats (Rattus norvegicus strain wistar). Experimental study with post-test control only group design. 16 rats were divided into 4 groups: normal group, conventional cigarette group (kretek) with 2.3 mg nicotine, 3 mg nicotine e-cigarette, and 0 mg nicotine e-cigarette. Trachea and heart of rats were prepared using HE-staining and observed with a light microscope with 400x magnification. All data were analyzed using One-way ANOVA, Kruskall Wallis and Post-Hoc tests. Cigarette smoke had a significant effect on tracheal goblet cell (ANOVA p=0.000) and left ventricular necrosis of the heart (Kruskal Wallis p=0.002). Post-Hoc test showed a significant difference in the number of goblet cells and left ventricular necrosis of the heart (p (-- removed HTML --) 0.005). This is due to the toxic materials such as carbon monoxide, propylene glycol, formaldehyde, nitrosamines, and other carcinogenic substances. E-cigarette and conventional cigarettes smoke could affect increasing of tracheal goblet cells and left ventricular necrosis of rat.